Human B-1 Cells and B-1 Cell Antibodies Change With Advancing Age - Rodriguez-Zhurbenko, Nely; Quach, Tam D.; Hopkins, Thomas J.; Rothstein, Thomas L.; Hernandez, Ana M. (Frontiers in Immunology, 2019)
Abstract Age-related deficits in the immune system have been associated with an increased incidence of infections, autoimmune diseases and cancer. Human B cell populations change quantitatively and qualitatively in the elderly. However, the function of human B-1 cells, which play critical anti-microbial and housekeeping roles, have not been studied in the older age population. In the present work, we analyzed how the frequency, function and repertoire of human peripheral blood B-1 cells (CD19+CD20+CD27+ CD38low/intCD43+) change with age. Our results show that not only the percentage of B-1 cells but also their ability to spontaneously secrete IgM decreased with age. Further, expression levels of the transcription factors XBP-1 and Blimp-1 were significantly lower, while PAX-5, characteristic of non-secreting B cells, was significantly higher, in healthy donors over 65 years (old) as compared to healthy donors between 20-45 years (young). To further characterize the B-1 cell population in older individuals, we performed single cell sequencing analysis of IgM heavy chains from healthy young and old donors. We found reduced repertoire diversity of IgM antibodies in B-1 cells from older donors as well as differences in usage of certain VH and DH specific genes, as compared to younger. Overall, our results show impairment of the human B-1 cell population with advancing age, which might impact the quality of life and onset of disease within the elderly population.